Aloe-emodin novel anticancer Herbal Drug - Khemkaran Ahirwar; Sanmati K. Jain (International Journal of Phytomedicine, 2011)
The electrochemical behaviour of the anticancer herbal drug emodin hydroxyanthraquinone present in Aloe vera leaves has a specific in vitro and in vivo antineuroectodermal tumor activity. The compound does not inhibit the proliferation of normal fibroblasts n or that of hemopoietic progenitor cells. The cytotoxicity mechanism consists of the induction of apoptosis, whereas the selectivity against neuroectodermal tumor cells is founded on a specific energy-dependent pathway of drug incorporation. Natural compounds that have traditionally been used to treat a variety of diseases for hundreds of years (1, 2, 3) . We assayed only those natural compounds that have already been proven to be nontoxic, and we evaluated their efficacy against highly malignant tumors that are not normally included in the classical screening assays.